Ant species on a facultative ant-plant (Macaranga tanarius) and their possible roles in herbivory protection - Wong, Zhi Hoong; Tan, Hong Liang; Yeo, Deniece Yin Chia; Yek, Sze Huei (Penerbit UMS, 2025)
Protective mutualism between ants and Macaranga genus plants ranges from obligate to facultative interactions. Unlike obligate ant-plant interactions, facultative mutualists like Macaranga tanarius lack specialized structures to house ant symbiont colonies but offer food rewards such as extrafloral nectary secretions and food bodies. These rewards attract opportunistic foraging ants that provide defense against insect herbivores. We hypothesized that the efficacy of this defense depended on the composition of the ant species. We assessed insect herbivory by recording leaf damage and monitored ant activity at different times of the day. We also conducted behavioral assays to test ants’ response toward offered wax-moth larvae prey (representing lepidoptera larva that causes most leaf-loss damage of M. tanarius). Ant community composition did not differ between day and dusk, with almost half of the species (48.4%) active at both times. Saplings with foraging ants showed a trend of higher leaf loss (mean = 2.13%) than saplings without ants (mean = 1.32%), contrary to our expectations, although this difference was not statistically significant. This could be due to the short observation time in this study, as herbivore attacks on leaf loss may be accumulated over a longer period. Most ant visitors on M. tanarius, which relied on herbivory diets, ignored the prey items; only the yellow crazy ant Anoplolepis gracillipes consistently attacked offered prey. Future research should be carried out over a longer period, and the abundance of ant species patrolling M. tanarius should be recorded to understand the potential roles of ants on these plants.